Open for business? Institutions, business environment and economic development - Robert Gillanders; Karl Whelan (University College Dublin, UCD School of Economics, 2010)
Recent years have seen a significant focus in the literature on growth and development on the idea that legal and political institutions are the key determinant of economic development. The main finding of this paper is that the focus on the primacy of legal and political institutions may be misplaced and that business-friendly economic policies (proxied for here by the World Bank's Doing Business indicator) are the key determinant of the level of income per capita. We find that a country's Doing Business rank dominates a range of measures of legal and political institutional quality as an explanatory variable for income per capita. We also find the Doing Business rank to be a key explanatory variable for economic growth and that previous findings assigning a significant role to educational attainment are not robust to the inclusion of this new indicator in growth regressions.
Keywords: 330